On spaces whose nowhere dense subsets are scattered - Julian Dontchev; David Rose (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to study the class of N-scattered spaces, i.e. the spaces whose nowhere dense subsets are scattered. The concept was recently used in a decomposition of scatteredness a topological space (X,τ)